Clinical exome sequencing in 509 Middle Eastern families with suspected Mendelian diseases: The Qatari experience. Issue 6 (27th March 2019) - Al‐Dewik, Nader; Mohd, Howaida; Al‐Mureikhi, Mariam; Ali, Rehab; Al‐Mesaifri, Fatma; Mahmoud, Laila; Shahbeck, Noora; El‐Akouri, Karen; Almulla, Mariam; Al Sulaiman, Reem; Musa, Sara; Al‐Marri, Ajayeb Al‐Nabet; et al.
Abstract : Background: Clinical exome sequencing (CES) is rapidly becoming the diagnostic test of choice in patients with suspected Mendelian diseases especially those that are heterogeneous in etiology and clinical presentation. Reporting large CES series can inform guidelines on best practices for test utilization, and improves accuracy of variant interpretation through clinically‐oriented data sharing. Methods: This is a retrospective series of 509 probands from Qatar who underwent singleton or trio CES either as a reflex or naïve (first‐tier) test from April 2014 to December 2016 for various clinical indications. Results: The CES diagnostic yield for the overall cohort was 48.3% ( n = 246). Dual molecular diagnoses were observed in 2.1% of cases; nearly all of whom (91%) were consanguineous. We report compelling variants in 11 genes with no established Mendelian phenotypes. Unlike reflex‐WES, naïve WES was associated with a significantly shorter diagnostic time (3 months vs. 18 months, p < 0.0001). Conclusion: Middle Eastern patients tend to have a higher yield from CES than outbred populations, which has important implications in test choice especially early in the diagnostic process. The relatively high diagnostic rate is likely related to the predominance of recessive diagnoses (60%) since consanguinity and positive family history were strong predictors of a positive CES.